2,2′-[4-Acetyl-1,3-phenylenebis(oxy)]diacetic acid - Wang, Jian-Guo (International Union of Crystallography, 2012)
In the title compound, C(12)H(12)O(7), the dihedral angles between the benzene ring and the mean planes of the 3-carboxymethoxy, 1-carboxymethoxy and acetyl substituents are 8.67 (7), 7.81 (6) and 10.3 (18)°, respectively. In the crystal, molecules are linked by typical carboxylic acid O—H⋯O hydrogen bonds, forming a zigzag chain. C—H⋯O interactions also occur.